2018
DOI: 10.24256/jpmipa.v4i2.260
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Baca Tulis Al-Quran dan Korelasinya terhadap Kemampuan Matematika Mahasiswa Prodi Tadris Matematika IAIN Palopo

Abstract: This research is quantitative correlations designed ex-post facto. The population is all students of mathematics department from 2012/2013 until 2014/2015 IAIN Palopo totaling 291 people. The sampling technique used was proportional random sampling with a sample of 73 students. The collection data using by documentation and test. The result showed that: (1). The overview of the literacy al - Quran is 53 students from 73 have a very high ability (72,5%). This means that the literacy Quran students in terms of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Besides that, many parents are more anxious if their children are poor on Mathematics, English or other sciences than demanding them to have better knowledge about Al-Qur'an8. It is in line with the finding of Hasri and Rahmah (2016) that the ability of students to understand mathematics is inversely proportional to the ability to understand Al-Qur'an recital, students' mathematical reasoning abilities are sometimes not equivalent to the literacy skills they have, so the dichotomy often occurs between students who can recite and write Al-Qur'an with students who have mathematical abilities.9 Another study conducted by Jumaeda (2017) found that the low ability to recite and write Al-Qur'an for students who are entering IAIN has implications for their low ability to learn and master Islamic sciences and this phenomenon has basically been detected from the beginning of student admission, where some large prospective students have difficulty in answering Arabic tests.10 Rohimin 2017found reality in the field that there were students until the end of the study before being able to recite Al-Qur'an when Practicing Field Experience (PPL), Proposal Seminars, and Munaqasah.11 Moreover, IAIN is an Islamic education institution that is capable in supporting its students and graduates to have better understanding about Al-Qur'an.…”
Section: Introductionsupporting
confidence: 92%
“…Besides that, many parents are more anxious if their children are poor on Mathematics, English or other sciences than demanding them to have better knowledge about Al-Qur'an8. It is in line with the finding of Hasri and Rahmah (2016) that the ability of students to understand mathematics is inversely proportional to the ability to understand Al-Qur'an recital, students' mathematical reasoning abilities are sometimes not equivalent to the literacy skills they have, so the dichotomy often occurs between students who can recite and write Al-Qur'an with students who have mathematical abilities.9 Another study conducted by Jumaeda (2017) found that the low ability to recite and write Al-Qur'an for students who are entering IAIN has implications for their low ability to learn and master Islamic sciences and this phenomenon has basically been detected from the beginning of student admission, where some large prospective students have difficulty in answering Arabic tests.10 Rohimin 2017found reality in the field that there were students until the end of the study before being able to recite Al-Qur'an when Practicing Field Experience (PPL), Proposal Seminars, and Munaqasah.11 Moreover, IAIN is an Islamic education institution that is capable in supporting its students and graduates to have better understanding about Al-Qur'an.…”
Section: Introductionsupporting
confidence: 92%
“…And it can be concluded that there is a positive direct influence on the ability to read the Qur'an, there is a positive influence on the ability to solve mathematical problems, there is a positive influence on the ability of mathematical connections. The results of significant research on the research of Hasri and Nur Rahma [17] show that the ability to read and write al-quran students in terms of knowing / recognizing Arabic letters, being able to read al-quran correctly has a significant correlation to mathematical skills. Students who have good mathematical skills have the ability to read and write the Al Quran as well.…”
Section: Resultsmentioning
confidence: 99%
“…Students who have good Al-Quran reading skills then have good Arabic writing skills as well. Furthermore, research conducted by Hasri and Nur Rahma [17] states that students' ability to read and write the Qur'an in terms of knowing / recognizing Arabic letters, being able to read the Qur'an correctly has a significant correlation with math skills. Students who have good math skills have the ability to read and write the Al-Quran well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapun menurut Hasri & Rahmah (2016) bahwa siswa yang mempunyai kemampuan membaca dan menulis dan dalam hal mengenal huruf arab itu bisa mempunyai kemampuan membaca Al-Qur'an dengan lancar dan juga mempunyai korelasi yang signifikan dengan keterampilan matematika (Syafri & Isran, 2021). Dengan demikian karena hasil penelitian ini menunjukkan adanya hubungan yang positif antara kemampuan membaca Al-Qur'an dengan kemampuan pemecahan masalah matematis maka siswa untuk lebih meningkatkan kemampuan membaca Al-Qur'annya agar mereka juga dapat meningkatkan kemampuan pemecahan masalah matematisnya.…”
Section: Madrasah Aliyah Pondok Pesantren Darun Naja Bengkulu Utaraunclassified